The effect of variety of agricultural comodity during vacuum pump frying - Irhami Adha; Ainun Rohana; Saipul Bahri Daulay (Jurnal Rekayasa Pangan dan Pertanian, 2013)
It appeared that many agricultural crops that has been processed further become more economics than before. One of the manufacturing process is frying. This research was the effect of variety of agricultural comodity during vacuum pump frying with potato (K1), sweet potato (K2) and taro (K3). This research was conducted at the Laboratory of Agricultural Engineering, Faculty of Agriculture, University of North Sumatra in November until December 2012 by completely randomized design non factorial. Parameters observed were were water content, yield and chips organoleptic test (taste, crunchness, and total acceptance). The results showed that the highest yield was K2 39,509% and the lowest was K1 23,512%, the highest water content was K1 2,715% and the lowest was K2 2,454%, while the highest organoleptic taste was K1 3,600 and the lowest was K2 and K3 3,167, the highest crunchness was K1 3,700 and the lowest was K3 3,500, the highest total acceptance was K1 3,477 and the lowest was K3 3,230. Key words : chips, vacuum frying, potato, swee potato, taro, yield, water content, organoleptic test.